Socio-economic conditions of Rishi community in Khulna City Corporation (KCC) - Rina Aktar; Rahul Halder (Indonesian Journal of Social Sciences, 2023)
Rishi is an untouchable community in society victims of various socio-economic disparities as well as inequalities. This study aimed at identifying the socio-economic conditions of the Rishi community in Khulna City, Bangladesh. The purpose of the study is to observe how to maintain their social life along with economic activities. Following the survey and case study (Mixed method) research design, a sample of 150 people was selected clustery from ‘Rishipalli’ (Ward No 24) as well as data were collected by administering a semi-structured questionnaire. Findings reveal that the majority of the respondent (98%) are Sanatan believers and accomplished primary level (32%) of education. Moreover, the maximum of respondents is cobbler (70%) as well as evolved dual income (44%). Furthermore, the higher percentage (43%) belong to monthly food expenditures ranging between BDT 3001 to BDT 5000, and the majority (56%) of the households have to bear medical costs of BDT 100 to BDT 500 per month during illness, 36 percent of the households seeking treatment from MBBS doctor. It is, therefore, strongly recommended that policymakers should develop effective measures to improve the conditions of Rishi people, emphasizing building awareness of their socio-economic issues.